Por trás das grades :reflexões sobre a experiência do ser apenado na situação de privação de liberdade - Campos, Jordana Celli B. (2006)
This research has resulted of investigations appeared from our work experience as psychologist in a prison of the state Rio Grande do Norte. It deals with the meeting with prisoner in the search for the rescue of the human being dignity, discovering the being that finds annulled by backwards of the prison. The current debate on the prisoners in Brazil has as focus the creation of efficient strategies in the combat to the criminal acts, not being worried in understanding the historical and social conditions in the context in which such acts develop. Our objective was to reach an understanding of the experience of the prisoner in the situation of freedom deprivation in Natal (RN) city. Its significant social relevance meets in emphasized thematic which intends to be revealing of the not-said one of these citizens. The epistemological space and the vision of adopted human being support in the humanist ideas of the Centered Approach in the Person and construct self, central nucleus of the personality theory proposal by Carl Rogers. We opt to the phenomenological method as way of access to the singularity of the experience of each one of the participants, supporting us in the strategy of the narrative as expression of the lived world. The results had pointed that the investigated experience is through suffering, that is, the way to be in the world of prisoner in the situation of freedom deprivation is felt by him/her as difficult to support. This reality is had by him/her as difficult to control, having a negative emotional repercussion for the self, leading the citizen to the alienation of his/her existential flow in these circumstances. The reflections produced in this work take us to consider that the punishment practices on behalf of a normalization of the behavior, linked to the recovery idea, do not meet to the intention of the arrests, that come demonstrating to the inefficacy of the objectives shown in the law as well as the loss of the human being dignity